Workplace Communication and English Language Anxiety: A Systematic Review - Liftita Widya Sari; Diki Darmawan; Muhammad Haikal Hidayatullah; Stevani Calvinia Eka Putri (Proceedings Law, Accounting, Business, Economics and Language, 2025)
ABSTRACT  English Language Anxiety (ELA) presents a significant psychological barrier impacting employee communication, confidence, and performance across diverse multicultural workplaces. This systematic literature review synthesizes empirical research from 2010 to 2025 to examine the causes, manifestations, organizational impacts, and intervention strategies related to ELA in professional contexts. Findings identify core psychological factors such as communication apprehension, fear of negative evaluation, test anxiety, and perceived linguistic inadequacy as primary contributors to ELA, leading to avoidance behaviors, reduced participation, and lowered organizational productivity. The review underscores the necessity of holistic interventions that combine language training with psychological support, inclusive organizational policies, empathetic leadership, and continuous professional development. Implicitly, ELA is framed as a structural issue embedded within educational, cultural, and organizational systems, requiring systemic efforts to foster psychologically safe and inclusive communication environments. This comprehensive analysis offers evidence-based recommendations for organizations aiming to mitigate ELA, enhance cross-cultural communication efficacy, and leverage linguistic diversity as a strategic advantage in globalized sectors.   ABSTRAK Kecemasan Bahasa Inggris (ELA), komunikasi di tempat kerja. Kecemasan berbahasa Inggris (ELA) merupakan hambatan psikologis yang signifikan yang berdampak pada komunikasi, kepercayaan diri, dan kinerja karyawan di berbagai tempat kerja multikultural. Tinjauan literatur sistematis ini mensintesiskan penelitian empiris dari tahun 2010 hingga 2025 untuk memeriksa penyebab, manifestasi, dampak organisasi, dan strategi intervensi yang terkait dengan ELA dalam konteks profesional. Temuan mengidentifikasi faktor psikologis inti seperti ketakutan komunikasi, ketakutan akan evaluasi negatif, kecemasan ujian, dan ketidakmampuan linguistik yang dirasakan sebagai kontributor utama ELA, yang mengarah pada perilaku penghindaran, berkurangnya partisipasi, dan menurunnya produktivitas organisasi. Kajian ini menggarisbawahi perlunya intervensi holistik yang menggabungkan pelatihan bahasa dengan dukungan psikologis, kebijakan organisasi yang inklusif, kepemimpinan yang berempati, dan pengembangan profesional yang berkelanjutan. Secara implisit, ELA dibingkai sebagai masalah struktural yang tertanam dalam sistem pendidikan, budaya, dan organisasi, yang membutuhkan upaya sistemik untuk menumbuhkan lingkungan komunikasi yang aman secara psikologis dan inklusif. Analisis komprehensif ini menawarkan rekomendasi berbasis bukti untuk organisasi yang bertujuan untuk mengurangi ELA, meningkatkan keefektifan komunikasi lintas budaya, dan memanfaatkan keragaman bahasa sebagai keunggulan strategis di sektor-sektor global.